Clam garden governance in the Gulf Islands National Park Reserve - McIntosh, Carrie (2016)
This project provides insights that inform the design of clam garden governance models including potential structures, processes and resources. The practice Western science calls “clam gardens” has played a significant role in First Nations communities of the Pacific Northwest for perhaps millennia. However, the gardens have not been tended for decades and restoration is now required. To achieve restoration, governance must focus on improving traditional and scientific knowledge of the gardens and on balancing inequalities that contributed to the depressed health of clam gardens. Leveraging a five-year clam garden restoration effort lead by Parks Canada and the WSÁNEĆ and Hul’qumi’num First Nations of British Columbia, this research explores these challenges through interviews with First Nations, researchers, and representatives from Gwaii Haanas National Park Reserve, Tla-o-qui-aht Tribal Parks, and Pacific Rim National Park Reserve. Results point to considerations for the development of clam garden governance models now and into the future.